A rapid and sensitive assay based on particle analysis for cell degranulation detection in basophils and mast cells. (September 2016) - Huang, Lufen; Pi, Jiang; Wu, Jianlin; Zhou, Hua; Cai, Jiye; Li, Ting; Liu, Liang
Graphical abstract: Sinomenine (SIN) is a purified alkaloid derived from the roots of Sinomenium acutum, a traditional Chinese medicinal plant, for treating rheumatism and arthritic diseases with allergy occurring according to clinical reports. For evaluation SIN-induced allergy in vitro and in vivo, a rapid, sensitive and low-cost method for determining the level of cell degranulation has been established in the study. The method was efficiently used for both of the drug-induced degranulation and systemic anaphylaxis by using cell culture medium and blood samples from animals. The data obtained from the method showed in accordance with the results by using classic β-hexosaminidase assay. The figure showed that plasma from sinomenine induced systemic anaphylaxis in rats was determined by particle analysis method. (A) Particle intensity analysis of the plasma from rats. (B) Particle distribution analysis of the plasma from rats. Abstract: The degranulation of mast cells and basophils is often initiated by a number of pathophysiological responses, especially in allergic and inflammatory conditions. Efficient techniques and methods for determining the level of such degranulation are highly demanded for laboratory and clinical studies. In this work, a rapid and sensitive assay based on the particle analysis of granules in RBL-2H3 cells, a cell line widely used as a convenient model system to study the degranulation of mast cells and basophils, was developed to detect cell degranulation using a Nanosight NS300 in light scatter mode and dynamic light scattering (DLS) on a Malvern Zetasizer Nano-ZS instrument. Using this method, drug-induced mast cell degranulation and systemic anaphylaxis were efficiently determined both in cell culture medium and blood samples from animals in the current study. This promising method is expected to be widely used for screening anti-allergic and anti-inflammatory drugs both in vitro and in vivo models, as well as for determining the level of mast cell degranulation of the patients in the clinic.